The Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Di PT. Alam Bumi Lestari - Yudha Dwiputra Putra; Lisa Lisa; Sutarno Sutarno; Dewi Anggraini; Supriyanto Supriyanto (Yayasan Literasi Sains Indonesia, 2022)
Product quality is an important part that must be considered in the sales process. Product quality is also an advantage of a product in meeting customer needs and desires. While the purchase decision is the attitude of consumers in determining one of several alternative choices. Quality products will greatly affect consumer purchasing decisions. Pt. Bumi Alam Lestari has 300 active customers. The formulation of the problem in this study,